Allogeneic hematopoietic stem cell transplantation for heavily pretreated patients with mycosis fungoides and Sezary syndrome. Issue 5 (23rd March 2022) - Cengiz Seval, Guldane; Sahin, Ugur; Bozdag, Sinem Civriz; Yuksel, Meltem Kurt; Topcuoglu, Pervin; Akay, Bengu Nisa; Sanlı, Hatice Erdi; Gurman, Gunhan; Toprak, Selami Kocak; Ozcan, Muhit
Abstract: Allogeneic hematopoietic stem cell transplantation (AHSCT) is a promising strategy for treatment of heavily pretreated mycosis fungoides/Sezary syndrome (MF/SS). Herein, we aimed to evaluate the outcomes of AHSCT for heavily pretreated patients with MF/SS retrospectively. This analysis included consecutive 19 patients with MF/SS who received 20 AHSCT between 2012–2021 in our transplant center. Eight patients have been previously reported. Fifteen patients had diagnosis of MF and referred to SS in five patients. In our cohort, all cases had advanced disease (stages IIB: n  = 1, IIIA: n  = 7; IIIB: n  = 4, IVA: n  = 4, and IVB: n  = 3). Nine patients (47.4%) had developed large cell transformation. Only two patients received AHSCT in complete response, one very good partial response and two partial response while the others had progressive disease ( n  = 15) before transplant. Seven (35%) patients were alive at the time of analysis, with a median follow up of 10.5 months (range, 0.3–113 months) after AHSCT. Nine patients (47.4%) died without disease relapse or progression. Non‐relapse mortality was 35.9% at 1 year and 26.9% at 3 years and thereafter. For all patients the probability of overall survival was 48.5% and 32.3% at 1‐ and 5‐year post‐transplant, respectively. AHSCT for MF/SS resulted in an estimated progression free survival of 45.4% at 1 year. Given the poor prognosis of patients not receiving transplants and in the absence of curative non‐transplantation therapies, our results support that AHSCT is able to effectively rescue 32.3% of the population of transplant eligible, heavily pretreated patients in 5 years.